Settlement of Estate Disputes in Review From a Legal Anthropological Perspective - Alim Tombili (Estudiante Law Journal, 2022)
This study aims to find out how the settlement pattern is used in the division of inheritance property in North Tamaila village and what factors are obstacles at the time of the division of inheritance property. Emperis type of research with a Case approach. result research shows the pattern of dispute resolution through several stages, the first stage which is known as  "Mopotihuloo Ahali Lo Wutato"(deliberation between family and heirs) is the first stage of conducting deliberations internally family between the extended family of the parties to the dispute but did not find the result of the agreement, the second stage is carried out, namely mediation, The inhibiting factor in the settlement of inheritance disputes consists of two factors, internal and external factors internal factors include low education, economy, and low religious understanding. Meanwhile, external factors factor in the lack of socialization from the government and counseling by traditional figures related to the system of distribution of inheritance both in the perspective of goGorontaloustomary law, civil law, and Islamic law.